Inequality and the Social Cost of Carbon - David Anthoff; Johannes Emmerling (Fondazione Eni Enrico Mattei (FEEM), 2016)
This paper presents a novel way to disentangle inequality aversion over time from inequality aversion between regions in the computation of the Social Cost of Carbon. Our approach nests a standard efficiency based Social Cost of Carbon estimate and an equity weighted Social Cost of Carbon estimate as special cases. We also present a methodology to incorporate more fine grained regional resolutions of income and damage distributions than typically found in integrated assessment models. Finally, we present quantitative estimates of the Social Cost of Carbon that use our disentangling of different types of inequality aversion. We use two integrated assessment models (FUND and RICE) for our numerical exercise to get more robust findings. Our results suggest that inequality considerations lead to a higher (lower) SCC values in high (low) income regions relative to an efficiency based approach, but that the effect is less strong than found in previous studies that use equity weighting. Our central estimate is that the Social Cost of Carbon increases roughly by a factor of 2.5 from a US perspective when our disentangled equity weighting approach is used.
Keywords: D63; H43; Q54; 330; Social Cost of Carbon; Inequality; Climate Change; Discounting; Equity Weighting; Integrated Assessment Model